SALAH PAHAM AL-MADAD DALAM AL-KUTŪB AL-SITTAH: - Nur Raihan; Ishak Suliaman (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
The word Al-Madad in the Al-Kutub Al-Sittah is defined as help, that is, help given by Allah in the form of assistance from angels and help from living humans. However, the Habaib created a poem in the Qasidah "Madad Ya Rasulullah" which was understood as asking for help from the Messenger of Allah, and was charged with an element of shirk in it. The main objective in this study is to examine the various meanings and understandings of the word al-Madad and the concept of Al-Madad in the Al-Kutub Al-Sittah. This study also provides answers to the intentions of Al-Madad in the qasidah "Madad Ya Rasulullah" as well as looking at various controversy issues in the practice of Habaib's dhikr. To achieve these objectives, this study uses a qualitative approach methodology with data collection techniques from interviews and observations at the Habaib dhikr activities in Jakarta. The results of this study found that the word Al-Madad can only be addressed to people who are still alive and able to provide help, not to people who have died. This case became one of the issues of controversy in terms of Tawāṣul and Istighatsah. Because basically the Habaib believe that the word Al-Madad in question is the meaning of hissy or not the true meaning of asking for help from people who have died. Finally, it can be concluded that caution is needed in understanding the purpose rather than recitation of remembrance and qasidah, because it can lead to things that are contradicted shari'ah.